Renewable Beta‐Elemene Based Cyclic Carbonates for the Preparation of Oligo(hydroxyurethane)s. Issue 17 (25th July 2022) - Maquilón, Cristina; Brandolese, Arianna; Alter, Christian; Hövelmann, Claas H.; Della Monica, Francesco; Kleij, Arjan W.
Abstract: Conversion of β‐elemene into new β‐elemene dicarbonates through epoxidation and halide salt‐catalyzed CO2 cycloaddition reactions is reported. Step‐growth polyaddition of this dicarbonate to five different, commercial diamines was investigated under neat conditions at 150 °C yielding non‐isocyanate‐based low molecular weight oligo(hydroxyurethane)s with 1.3≤ Mn ≤6.3 kDa and 1.3≤ Ð ≤2.1, and with glass transition temperatures ranging from −59 to 84 °C. The preparation of one selected polyhydroxyurethane material, obtained in the presence of Jeffamine® D‐2010 was scaled‐up to 43 g. The latter, when combined in a formulation using Irgacure® 2100 and Laromer® LR 9000 allowed the preparation of coatings that were analyzed with several techniques showing the potential of these biobased oligourethanes towards the preparation of commercially relevant materials. Abstract : Naturally : Biobased β‐elemene was probed as a renewable precursor for the synthesis of non‐isocyanate based polyurethane coatings. Conversion of this terpene into its bis‐cyclic carbonate was examined, followed by polycondensation with commercially relevant diamines thereby providing oligourethanes as pre‐polymers. One of these was tested extensively and found to be potentially suitable as a starting point for new coating formulations using a dual curing approach.